The new paradigm in animal testing – “3Rs alternatives” - Wen, Tsin Poh; Stanslas, Johnson (Academic Press, 2024)
Regulatory studies have revolutionised over time. Today, the focus has shifted from animal toxicity testing to non-animal for regulatory safety testing. This move is in line with the international 3Rs (Replacement, Reduction, and Refinement) principle and has also changed the regulator's perspective. The 3R principle has stimulated changes in policy, regulations, and new approaches to safety assessment in drug development in many countries. The 3Rs approach has led to the discovery and application of new technologies and more human-relevant in vitro approaches that minimise the use of animals including non-human primates, in research and improve animal welfare. In 2016, the European Medicines Agency published the Guidelines on the principles of regulatory acceptance of 3Rs testing approaches, followed by a conceptual paper in 2023 to align with current 3R standards. Additionally, the United States Food and Drug Administration passed new legislation in 2023 that no longer requires all new human drugs to be tested on animals, which will change the current testing paradigm. This review paper provides the adoption of the 3Rs and the current regulatory perspective regarding their implementation.